ASPEK DIMENSI TANGIBLE DAN RESPONSIVENESS PADA PELAYANAN BUS SURABAYA SIGHTSEEING AND CITY TOUR - Sheidy Yudhiasta; Arnandhia Fatimah Azzahra (STAH Dharma Sentana Sulawesi Tengah, 2026)
The city of Surabaya has cultural heritage and historical buildings that can be used as history-based tourism. The Surabaya City Culture, Youth and Sports and Tourism Office is trying to introduce the attraction of Surabaya City tourism through the Surabaya Sightseeing and City Tour Bus. This study aims to analyze the tangible aspects and responsiveness of the Surabaya Sightseeing and City Tour Bus using a qualitative descriptive approach. Data collection techniques use interview, observation and documentation techniques. The research results show that the tangible aspects of the bus reservation system of SSCT, the appearance of tour guides and the infrastructure of the SSCT Bus have been running well. In the aspect of responsiveness, it shows how tour guides respond well to tourists who want to receive services, tour guides also perform services appropriately and tourist complaints are responded well to by tour guides.